Effects of Foliar Application of Micronutrients On Growth, Yield and Quality of Sweet Orange (Citrus Sinensis (L.) Osbeck) (Bangladesh Journal of Botany, 2022)
Calcareous and alkaline nature of soil hinders smooth up take of micronutrient from soil. Hence, the impact of foliar feeding of micronutrients (Zn, Fe, B, Cu) in different combinations on growth, yield and quality of sweet orange cv. Mosambi in a non-conventional citrus growing area was evaluated. Results revealed that treatment combination of Zn @ 0.5% + Fe @ 0.2% + B @ 0.3% + Cu @ 0.1% (T9) followed by B @ 0.3% + Fe @ 0.2% (T6) and Zn @ 0.5% + B @ 0.3% (T7) was most effective for improving growth of Mosambi plants in terms of shoot length, leaf number, leaf area as well as photosynthetic efficiency of the plant. The yield per plant was also obtained maximum in T9 (14.94 kg). Further, fruit quality attributes in terms of TSS, total sugar, flavonoids, ascorbic acid content as well as antioxidant capacity of the fruit were recorded maximum in T9 with at par result in T6. Therefore, three foliar spray of Zn @ 0.5% + Fe @ 0.2% + B @ 0.3% + Cu @ 0.1% from May-July can be recommended to get maximum yield with better fruit quality from mosambi orchard under non-conventional track having calcareous and alkaline nature of soil.Bangladesh J. Bot. 51(1): 57-63, 2022 (March)